Efforts To Improve Teacher Discipline In Teaching Attendance In The Class Through The Implementation Of Reward And Punishment At SDN 019 Tanjung Sawit, Tapung District - Hayati, Hayati (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Improving the quality of learning in schools really depends on several factors. A very important factor, among others, is the implementation of school culture towards improving quality. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of discipline, including the discipline of teachers in their presence in class during the teaching and learning process. To improve teacher discipline, efforts can be made in various ways. The research aims to improve teacher discipline in teaching presence in class through the application of reward and punishment. In this School Action Research (PTS), action was attempted in the form of implementing Reward and Punishment for teachers at SD Negeri 019 Tanjung Sawit, Kampar Regency. This research was carried out in two cycles, because from the results of research and data analysis, it turned out that in the second cycle, discipline teachers' attendance in class during the teaching and learning process increased and met the indicators that had been set at 75%. From the results of this research, it can be concluded that improving teacher discipline in class attendance during teaching and learning activities can be done by implementing Reward and Punishment for teachers.